Cropping Patterns for Drylands of India- An Agro-Climatic Approach - Singh, R P; Singh, Atar; Ramakrishna, Y S (Annals of Arid Zone, 2016)
An agro-climatic approach to rational crop planning on the drylands of India. representing various soil groups, has been suggested in this paper. ~t almost all stations. improved varieties of the conventional crops hating higher yield potential and better moisture utilisation efficiency have been identified. Fcr the arid region (Zone I), having moisture index range of -100 to -66.7, new and remunerative crops like sonflower, castor and cowpeas have been indicated, Possibilities of substituting ti1 with sunflower exist in Jodhpur and Anand regions., At Bellary, rabi jowar and safflower have shown great promise. Yields to the extent of 300 percent could be increased in case of rabi jowar by advancing the sowing date to September. On the red soils of Anantpur, Hyderabad and Hebbal, double cropping in the kharif season is a possibility with promising short duration varieties in years when early monsoon is received. Cotton and safflower could be popularised on the black soils. Byfar, in the semi-arid region (Zone II) with a moisture index range of -33 to -66 the existing cropping intensity could be pushed up with prope. moisture corservation and water harvesting procedures, to make double cropping a distinct possibility. In the dry sub-humid region (Zone HI), with moisture index range of -33 to 0, two good crops could be taken with advantage, with suitable manipulations agro-techniques. Stability in crop production in Zones 11 and 111 if achieved will ultirnatety stabilise agricultural production in the country, for these regions contribute a major share to the total out put of foodgrains. In the moist sub- humid region (Zone IV), with moisture index range of 0 to +20, double cropping is in vogue, but with suitable agronomic manipulation including water management multiple cropping could be practiced.